(Pyrazines :Syntheses, analysis and its flavour properties) - Timur Antara, Ngakan (Balai Besar Industri Agro, 1991)
Numerous pyrazines compounds have been isolated from various food stuffs.Studies have demostrated the importance of these compound in the flavor of heated and toasted food,and of course they are produced by maillard reaction.The review is concerned with their syntesis,analysis nd flavour properties.